Pandangan Kepala KUA Se-Kota Yogyakarta Terhadap Shighat Taklik Talak - Fitriah Elkarimah, Mia; Asriani, Devi (Tasyri' : Journal of Islamic Law, 2022)
In the wedding tradition, after the contract (ijab qabul), the groom reads sighat taklik which is listed in the marriage certificate. The legal consequences for the groom must fulfill all the contents of the promise contained in the shigat taklik, while for the bride, it can be used as a reason to file for divorce to the Religious Court, if violated by the male partner. The purpose of this study was to find out the views of the heads of KUA throughout the city of Yogyakarta regarding the reading of sighat taklik. The approach used in this research is a normative approach. Data collection methods used in this study were interviews and documentation. The article found that: 1) Some of the heads of KUA throughout the city of Yogyakarta said that sighat taklik talak is mandatory because it is a legal umbrella for a wife so that her husband does not act arbitrarily to her. Others think that sighat taklik talak is not obligatory to read because it interferes with the solemnity and sacredness of the marriage contract procession. 2) Regarding its effect on reducing the divorce rate, three heads of KUA are of the opinion that it is not effective because there are still many wives who file for divorce from their husbands because their husbands violated sighat taklik talak, while the other eleven are of the opinion that whether or not it is effective in reducing the divorce rate, does not have to be caused by husband violates sighat sighat taklik divorce. Keywords: sighat, taklik talak, head of KUA.